Screening methods to measure antioxidant activities of phenolic compound extracts from some varieties of Thai eggplants - Chanasut U. (2014)
Phenolic compounds and their antioxidant activities from fruits of eleven Thai eggplant varieties were determined. Freeze dried samples were extracted in 70% methanol and their total phenolic contents were measured. Antioxidant activities of the crude extracts were evaluated using three different assays: the DPPH (diphenyl-1-picrylhydrazyl) assay, the β-carotenoid bleaching assay, and the ABTS+ (2,2'-azinobis 3-ethylbenzothiazoline-6-sulfonic acid) assay. The antioxidant activities were expressed as gallic acid equivalents (GAE) to standardize these methods to allow for data comparisons. The three antioxidant assay methods give different antioxidant activity trends. Phenol contents of the eggplant extracts were related to their antioxidant activities measured by ABTS+ and DPPH assay. In contrast, the results measured by the β-carotenoid bleaching assay were not related to the phenol contents of the extracts. On the basis of DPPH results, Solanum torvum has both the highest total phenolic content and total antioxidant activity.